African American and Asian American Contacts and Confrontations: A Model of Fashioning (Ethnic) Masculinity - Šesnić, Jelena (2005)
The article traces some structual parallels entailed in similar but distinct historical predicaments faced by Asian American and African American men, which gets translated in some of the texts from Asian American canon as a narrative of cultural exchange, competition and ambiguous borrowing.
Projekt MZOS
ENG